The Effect of Stock Selection Ability, Market-Timing Ability, and Fund Cash Flow on the Performance of Sharia Equity Mutual Funds (Study During the Covid-19 Pandemic, 2020-2021) - Budi, Rakhmad Pambudi; Prasaja, Mahendra Galih; Utomo, Agus Saur (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
The COVID-19 pandemic posed significant challenges to global capital markets, including Islamic equity mutual funds in emerging economies such as Indonesia. This study investigates the effects of stock selection ability, market-timing ability, and fund cash flow on the performance of Islamic equity mutual funds during the 2020–2021 pandemic period. Using monthly NAV data from 39 Sharia-compliant equity mutual funds registered with Indonesia’s Financial Services Authority (OJK), we applied multiple linear regression models with the Sharpe index as a performance proxy. The results show that all three variables—stock selection ability, market-timing ability, and fund cash flow—exert a positive and statistically significant influence on mutual fund performance. These findings highlight the crucial role of fund managers' strategic competencies during crisis periods and reinforce the importance of liquidity dynamics in Sharia fund resilience. This study contributes to the Islamic finance literature by empirically validating how investment decision-making quality affects Sharia mutual fund outcomes in crisis contexts. Furthermore, it offers a methodological foundation for comparative international studies on Islamic versus conventional mutual fund performance under systemic shocks. Future research may expand this framework across different Islamic financial jurisdictions or explore non-linear relationships using advanced econometric models.